(untitled) (Biological Sciences - PJSIR, 2007)
. Study of th e core sa111pl es of powder and c l ay (< 2 t ) fraction grai n size fro111 coal fi eld of Thar, Sind h, Paki stan , for t h e m i nera l co111posi ti on , kaol i n izarion processes and en v i ron m ents of the deposi tion , i nd i cat ed both types of kaol i n i te i .e. we ll crysta ll i ne an d degraded , as t h e 111ai n con st i tuen ts i n bot h t h e sam p l es. Quartz and anat ase were i n su b-o rdi n ate amou nts i n rando111 powder, and d ick i t e i n c l ay fract i on . A uth i gen i c a nd degraded , both t y pes o f kaol i n i te, were present i n th e sed i111ent. Di ck i t e showed i t s p resence i n restr i cted sa111pl es, whereas anatase (Ti02 ), detr i t a l of a uth igen i c origi n , were presen t i n t h e w ho l e-rock samples. It i s i nferred t hat leach i n g of kaol i n i te and suffi ci ent a mou nt of t i tan i u m from the Tharpark ar gran ite prod u ced auth igen ic anatase and some a111ou n t of detr i ta l anatase was cont ri buted by the weat heri n g of Nagarparkar gran i te. Presen ce of detri tal 111i n era l s i.e. q uartz, kaol i n i te, a natase and a l so the i ron ox ide, su ggest a near shore deposit i on, und er red uci ng a nd 111icro-ox i dizi n g en v i ron111e n ts.